Systematic review of teaching methods in language education: trends and innovation - Mohd Noor, Nur Atikah; Mahamod, Zamri; Nasri, Nurfaradilla Mohamad (International Journal of Evaluation and Research in Education (IJERE), 2025)
This systematic literature review (SLR) examines the developing pedagogical methods in language instruction, emphasizing modern practices, technological advancements, and cultural diversity. The research seeks to fill significant gaps in the literature by examining effective pedagogical strategies that improve language acquisition results. In accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) methodology, a systematic search of the Scopus and Web of Science (WoS) databases was performed, focusing on publications published from 2022 to 2024. 30 primary studies were examined through topic synthesis and integrative analysis. The findings are categorized into three themes: i) contextualized and adaptive teaching methods in language education: balancing traditional approach and innovation; ii) impact of innovative teaching on language learning: technology and student engagement; and iii) cultural diversity’s impact on language education and engagement. The results underscore the imperative of modifying teaching strategies according to different situations and incorporating technology to enhance engagement and results. Furthermore, culturally sensitive techniques were demonstrated to improve inclusivity in multilingual classrooms. These insights are pertinent to academic and professional settings, indicating widespread significance for enhancing communication and cross-cultural skills. Future research should investigate the long-term effects of these initiatives and ensure equal access to educational resources and teacher training.